Research and field tests of staged fracturing technology for casing deformation sections in horizontal shale gas wells - Shimeng Liao; Yu Sang; Yi Song; Bo Zeng; Wang Liu; Lei Yang (Natural Gas Industry B, 2018)
Horizontal shale gas well fracturing is mostly carried out by pumping bridge plugs. In the case of casing deformation, the bridge plug can not be pumped down to the designated position, so the hole sections below the deformation could not be stimulated according to the design program. About 30% of horizontal shale gas wells in the Changning and Weiyuan Blocks, Sichuan Basin, suffer various casing deformation after fracturing. Previously, the hole sections which could not be stimulated due to casing deformation were generally abandoned. As a result, the resources controlled by shale gas wells weren't exploited effectively and the fracturing effect was impacted greatly. There are a lot of difficulties in investigating casing deformation, such as complex mechanisms, various influencing factors and unpredictable deformation time. Therefore, it is especially important to seek a staged fracturing technology suitable for the casing deformation sections. In this paper, the staged fracturing technology with sand plugs inside fractures and the staged fracturing technology with temporary plugging balls were tested in casing deformation wells. The staged fracturing technology with sand plugs inside fractures was carried out in the mode of single-stage perforation and single-stage fracturing. The staged fracturing technology with temporary plugging balls was conducted in the mode of single perforation, continuous fracturing and staged ball dropping. Then, two kinds of technologies were compared in terms of their advantages and disadvantages. Finally, they were tested on site. According to the pressure response, the pressure monitoring of the adjacent wells and the microseismic monitoring in the process of actual fracturing, both technologies are effective in the stimulation of the casing deformation sections, realizing well control reserves efficiently and guaranteeing fracturing effects. Keywords: Shale gas, Horizontal well, Casing deformation, Staged fracturing, Staged fracturing with sand plug, Staged fracturing with temporary plugging ball, Field test, Sichuan Basin, Changning and Weiyuan Blocks